(untitled) (Journal of Partial Differential Equations, 2007)
In this paper, by establishing the boundedness results of singular integral operators and linear commutators, we obtain the global regularity, in homogeneous Morrey-Herz spaces, of strong solutions to nondivergence elliptic equations with VMO coefficients.